EFEKTIVITAS METODE SAS (STRUKTURAL ANALITIK SINTETIK) TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA FASE A SDN 3 MASBAGIK SELATAN - Anik Kholida; Husnul Mukti; Baiq Rizki Hidayati; Moh. Irfan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The main problem in this study is the low initial reading ability of phase A students at SDN 3 Masbagik Selatan. This study aims to determine the effectiveness of the SAS (Structural Analytical Synthetic) method in improving the initial reading ability of phase A students at SDN 3 Masbagik Selatan. The research method used is an experiment with a one group pretest-posttest design. Data collection techniques were taken by giving pretests and posttests in the form of multiple choice tests. Data analysis used in this study is the normality test and hypothesis test. Based on the results of the normality test on the pretest value shows that lhitung < thitung (0.165 < 0.190), while the posttest value shows that lhitung < thitung (0.137 < 0.190) so that it means the data is normally distributed. Furthermore, based on the results of the hypothesis test obtained thitung > ttabel (10.735 > 1.725), the hypothesis reads